Nonlinear Simulation of Stress-Strain Curve of Infill Materials Using PLP Fit Model - Pradhan, Prajwal Lal; Murty, C.V. R.; Hoiseth, Karl Vincent; Aryal, Mohan Prasad (Journal of the Institute of Engineering, 2009)
This paper puts forward an idealization of stress-strain curve of structural materials like bricks, and mortar. In this model, below yield limit, the pattern of the stress-strain relationship is assumed to be linear i.e. modulus of elasticity remains unchanged, whereas beyond the limit, the relationship is supposed to be curvilinear. A quadratic stress function is assumed to formulate the stress-strain curve passing through the points of yield stress sy and ultimate stress su. Experimental investigation on the cube-tests of specimen for brick samples and mortar cubes are also presented for the verification of idealized stress-strain relationships. Journal of the Institute of Engineering, Vol. 7, No. 1, July, 2009 pp. 99-110 doi: 10.3126/jie.v7i1.2067